2022
DOI: 10.3389/fpsyt.2022.1018440
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and its correlates of the community toward mental illness in Mattu, South West Ethiopia

Abstract: BackgroundThe magnitude of mental health conditions in the general population was high in low-resource settings like Ethiopia. This was accompanied by little evidence on knowledge, attitudes, and related determinants in the general population. Therefore, the current survey is planned to assess the knowledge, attitude, and related factors of the community toward mental illness in Mattu, South West Ethiopia.ObjectivesOur study aimed to assess the knowledge, attitude, and related factors of the community toward m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
(42 reference statements)
1
4
0
Order By: Relevance
“…There is no association between good knowledge and negative attitudes. 30 In a study by Birkie et al, poor knowledge was associated with unfavourable attitude, which is consistent with our findings. 22 Most survey participants are willing to live with and work with individuals facing mental health challenges and maintain friendships with them.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There is no association between good knowledge and negative attitudes. 30 In a study by Birkie et al, poor knowledge was associated with unfavourable attitude, which is consistent with our findings. 22 Most survey participants are willing to live with and work with individuals facing mental health challenges and maintain friendships with them.…”
Section: Discussionsupporting
confidence: 93%
“…Recent research suggests that young adults have a tendency to over-identify with depression, 28 , 29 potentially because of increased exposure to mental health education through social media campaigns that aim to raise awareness about depression and suicide. 30 Other studies had similar results where younger age was associated with a low level of knowledge and a low level of stigma related knowledge. 21 Other studies found no association between age and level of knowledge.…”
Section: Discussionmentioning
confidence: 72%
“…This study found that more than fifty percent of individuals have negative or less supportive attitudes toward people living with mental illness, namely 52 (52.52%). Previous studies found that majority of people had negative attitude toward people living with mental illness (Despande et al, 2020;Jarso et al, 2022;Puspitasari et al, 2020;Saragih et al, 2013). This study result was similar to the prior studies.…”
Section: Discussionmentioning
confidence: 97%
“…Autism has a wide range of symptoms, levels of severity, and is often comorbid with other conditions. Insufficient diagnostic capacity and management of autism increases the need for more research to help address these challenges [ 79 81 ]. It is possible that the growing awareness and advocacy for autism, as well as increased funding from charitable organizations, have contributed to its status as one of the most studied CAMH disorders [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…This attitude is not only prevalent in low-income countries but also in high-income countries such as the United Kingdom and Slovenia [ 91 , 92 ]. The poor attitudes could be attributed to HCWs’ lack of knowledge about CAMH, which can lead to misconceptions and stigma toward CAMH [ 79 ]. Cultural norms and beliefs may stigmatize CAMH, leading to reluctance to seek or provide appropriate CAMH care [ 34 , 93 ].…”
Section: Discussionmentioning
confidence: 99%